Role of exosomal noncoding RNA in esophageal carcinoma - Si, Mao-Yan; Rao, Ding-Yu; Xia, Yao; Sang, Cheng-Peng; Mao, Kai-Yun; Liu, Xiang-Jin; Zhang, Zu-Xiong; Tang, Zhi-Xian (Frontiers in Oncology, 2023)
Esophageal cancer is one of the most prevalent malignant tumors with high mortality. Understanding its pathogenesis and identifying early diagnostic biomarkers can significantly improve the prognosis of esophageal cancer patients. Exosomes are small double-membrane vesicles found in various body fluids containing various components (DNA, RNA, and proteins) that mediate intercellular material exchange and signal communication. There is growing evidence that exosomes and their components are involved in cancer growth, metastasis, and angiogenesis and can also be used as diagnostic and prognostic markers. This article reviews the recent progress in exosomes' role in esophageal cancer, including research progress, diagnostic value, proliferation, migration, invasion, and drug resistance.